Dinamika Moderasi Beragama: Studi Pemahaman Moderasi Beragama oleh Organisasi Ekstra Mahasiswa - Bakhrul Ulum (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
Religious moderation in the context of extracurricular student organizations in Indonesia. The background of this study is based on the importance of developing a moderate religious attitude as a middle way to avoid extremism that can threaten social harmony and national unity. This study aims to explore the understanding and implementation of religious moderation in three main extracurricular student organizations: PMII, HMI, and GMKI. The research method uses a qualitative approach with descriptive field research techniques. Data were collected through observation, in-depth interviews, and documentation which were then analyzed qualitatively to obtain a complete picture of the phenomenon being studied. The results of the study indicate that although the concept of religious moderation is accepted and understood by members of the organization, its implementation in organizational activities still faces challenges, especially in terms of empathy and tolerance between members. Other findings emphasize the importance of the values of Ahlussunnah wal Jama'ah and nationalism as a basis for strengthening religious moderation. In conclusion, religious moderation is the main prerequisite for creating a harmonious and peaceful society in Indonesia. However, efforts are needed to strengthen the implementation of religious moderation in extracurricular student organizations through continuous education and increasing collective awareness. This study provides strategic recommendations to strengthen the values of religious moderation in order to contribute to national harmony.